Employee ownership and employee involvement at work : case studies - Berry, Daphne; Kato, Takao, 1954- (Emerald Publishing Limited, 2018)
With a growing prominence of sophisticated econometric research in a much-expanded field of New Economics ofParticipation (NEP), it is of particular value to learn about real-world examples of participatory and labor-managed firms in the advanced market economies through extensive case studies. In this volume of 'Advances in the Economic Analysis of Participatory and Labor-Managed Firms', the authors present such case studies. The real-world examples of participatory organizations described vividly in this volume will help researchers in NEP to design empirical strategies better, and to interpret their econometric results more sensibly. Furthermore, they will help policymakers and practitioners in their efforts to construct better public policy and design management practices.
Includes index.
Keywords: Management -- Employee participation -- Case studies.; Employee ownership -- Case studies.; Business & Economics -- Labor.; Employee-ownership & co-operatives.; elektronické knihy; electronic books